Water use efficiency of Cupressus gigantea is higher in mountain slope habitats compared to riverside habitats - Yueliang Jiang; Li Luan; Youlu Zuo; Shengyun Liu; Qiaoling He; Jingyu He; Ruru Wu; Gaoming Jiang; Meizhen Liu (PLoS ONE, 2025)
Cupressus gigantea is an endemic species of the Yarlung Zangbo River in Tibet, China, and is designated as a national key protected wild plant species. It is uniquely distributed in the specific sections from Jiacha County to Danniang village Milin City along Yarlung Zangbo River in various habitats such as the waterline along the Yarlung Zangbo River, terraces, and mountain slopes. In this study, we utilized stable isotope technology(δD, δ18O, and δ13C), combined with the IsoSource model, to quantitatively determined the sources of water absorption and the water use efficiency of C. gigantea in various habitats, including riverside area, terraces and mountain slopes. The results showed that the content of soil total nitrogen, soil nitrate nitrogen, soil ammonium nitrogen, and soil organic carbon are significantly higher on mountain slope than in the other two habitats, while the total carbon content, water content, and total nitrogen content of C. gigantea leaves are significantly lower on mountain slope than in the other two habitats (P < 0.05). The water use efficiency (WUE) of C. gigantea in the mountain slope habitats is 107.8 μmol mol-1, which is significantly higher than that of other habitats (P < 0.05), with the WUE of C. gigantea in the riverside habitat being the lowest at 35.7 μmol mol-1. C. gigantea distributed on the mountain slope and terrace uses soil water as the main water source. During the normal rainy season, the proportion of soil water utilization is the highest, accounting for more than 60%; in the dry season, the utilization of river water and groundwater increases, while soil water utilization decreases. C. gigantea distributed along the riverside mainly absorbs water from the Yarlung Zangbo River, about 63%. In August when the rainfall increases in the rainy season, the use of soil moisture increases, and in the dry season, river water becomes the main water source. This indicates that with the alternation of rainy and dry seasons, the water absorption sources and strategies of C.gigantea adjusted accordingly. The research results provide an important scientific basis for the protection and management measures of the C. gigantea population.